Catalytic cracking catalyst and preparation method thereof
By modifying the catalysts for components such as ZSM-5 molecular sieve, titanium-containing composite binder and clay, the catalyst structure is improved by using titanium tetrachloride waste liquid to solve the problem of low yield in the treatment and catalytic cracking of polypropylene catalyst waste liquid, achieving efficient heavy oil conversion and low-carbon olefin yield.
Patent Information
- Application Number
- CN202311423245.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-30
AI Technical Summary
The problem of handling waste liquids containing titanium tetrachloride generated during the preparation of polypropylene catalysts, as well as the problem of high yield of heavy oil, high coke and low carbon olefins during the catalytic cracking process.
The catalytic cracking catalysts with modified ZSM-5 molecular sieve, titanium-containing composite binder and clay are prepared by spray drying and calcining processes, and the pore structure and activity of the catalyst are improved by using titanium, chlorine and organic matter in the titanium tetrachloride waste liquid.
It effectively reduces the yield of heavy oil and coking tendency, while improving the yield of low-carbon olefins, and improving the reaction selectivity and use performance of the catalyst.
Smart Images

Figure BDA0004522236090000181 
Figure BDA0004522236090000191
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oil refining catalysts and additives, and relates to a catalytic cracking catalyst, and in particular to a catalytic cracking catalyst for reducing coke yield and increasing light olefin yield, and a preparation method thereof. Background Art
[0002] In the process of industrial production of polyolefins, the widely used catalyst is mainly Ziegler-Natta catalyst, which is a titanium catalyst. Regarding the preparation of titanium polyolefin catalysts, for example, patent CN102336851B discloses a propylene polymerization catalyst, including magnesium, titanium, halogen and internal electron donor compounds diisobutyl phthalate, diethyl phthalate or di-n-butyl phthalate and a mixture of succinate; patent CN107434832B discloses a propylene polymerization catalyst, mainly composed of alcohol magnesium compounds, titanium compounds and phosphate electron donor compounds. The common method for preparing titanium catalysts at present is: firstly prepare magnesium halide alcohol compound, for example, after magnesium halide and alcohol are heated and dissolved, high pressure ejection or high speed stirring is used, and the method of solidifying into microsphere particles in a cooling medium is obtained, and the specific steps are referred to the relevant description in CN1110281A; then the magnesium halide alcohol compound particles are reacted with halogen-containing compounds such as titanium tetrachloride to prepare a magnesium-supported catalyst, during which various promoters can be added for modification. In the above-mentioned catalyst preparation process, a large amount of titanium tetrachloride needs to be used, and the excess ratio is very large. At the same time, the solid catalyst component obtained needs to be washed with a hydrocarbon solvent (such as hexane) to remove the unloaded titanium tetrachloride therein. Therefore, in the polyolefin catalyst production process, after the catalyst solid is separated and precipitated, a large amount of catalyst mother liquid containing at least one of titanium tetrachloride, unreacted hydrocarbons, unreacted halogenated alkoxy titanium, alkoxy magnesium, and unreacted esters will be produced. A large amount of waste liquid containing titanium tetrachloride is produced in the titanium-based polypropylene catalyst preparation process, which contains a small amount of alkoxy titanium complex (for example, about 2-5%), a small amount of lipids, and n-hexane in addition to titanium tetrachloride (at least 80%). If the waste liquid is directly discarded, it is bound to cause environmental pollution and waste of resources, so it is necessary to make effective use of it.
[0003] Regarding the treatment and utilization of waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalyst, CN106277046B discloses a method for treating waste liquid containing titanium tetrachloride, wherein the waste liquid contains titanium tetrachloride, an organic solvent, and halogenated alkoxy titanium and / or alkoxy titanium. The method comprises: (1) contacting the waste liquid containing titanium tetrachloride with water for hydrolysis; and (2) distilling the waste liquid after hydrolysis and collecting titanium-containing compounds from the remaining material.
[0004] CN112723430 A discloses a method for treating and recovering waste liquid from the production of polyolefin catalysts, the method comprising: (1) introducing the waste liquid from the production of polyolefin catalysts and hydrolysis water into a hydrolysis reactor for continuous hydrolysis reaction to obtain a gas phase stream I and a solid-liquid mixed phase stream; (2) incinerating the solid-liquid mixed phase stream to obtain a gas phase stream II and a stream containing TiO 2 (3) removing dust from the gas phase stream I and the gas phase stream II to obtain a gas phase stream III and a solid phase stream containing TiO 2 (4) subjecting the gas phase stream III to hydrochloric acid absorption treatment. The method realizes the pollution-free discharge treatment process of the waste liquid produced by the polyolefin catalyst, and also realizes the resource recovery of Cl and Ti elements in the waste liquid.
[0005] Regarding the preparation of titanium sol, titanium-containing molecular sieve, titanium-containing catalytic material, titanium-containing catalyst and additive by titanium tetrachloride, CN107866211 B discloses a TiO 2 Sol and catalytic cracking catalyst and method for preparing the same, the TiO 2 The titanium-chloride molar ratio of the sol is (0.2-0.6):1; and the TiO 2 Sol corrosion rate ≤ 1g / m 2 ·h, pH value is 5-8, viscosity ≥1000mPa·s at 20℃. 2 Because of its high viscosity, low corrosion rate and high pH value, the sol, when used as a binder for preparing catalytic cracking catalysts, is beneficial to increase the specific surface area of the catalytic cracking catalyst, improve the sphericity of the catalytic cracking catalyst, and enhance the activity of the catalytic cracking catalyst, improve the product distribution of the catalytic cracking reaction, and is mainly beneficial to the production of the target product gasoline.
[0006] CN102114429 B discloses a method for increasing the B acid content of a ZSM-5 molecular sieve and achieving increased production of light olefins. The method comprises modifying the ZSM-5 molecular sieve with iron and titanium simultaneously. After modification, the mass ratio of iron to titanium in the molecular sieve is 0.3-3:1, thereby improving the catalytic reactivity of the molecular sieve, promoting the conversion of long-chain alkanes and aromatic hydrocarbons with long-chain alkyl side chains, such as isopropylbenzene, and achieving the effect of significantly increasing the yield of light olefins.
[0007] CN109694721 B discloses a macroporous kaolinite and its preparation and application. The macroporous kaolinite contains a modified metal, and the average pore diameter is 2-50nm. The pore volume of pores with a pore diameter of 10-50nm accounts for more than 80% of the total pore volume. The modified metal is one or more of alkaline earth metals, titanium and zirconium. The preparation method of the macroporous kaolinite comprises: first calcining the kaolinite; forming a mixture of the kaolinite after the first calcination and a first acid, water, and an optional modified metal compound, performing a first treatment, then performing a second calcination, and then forming a mixture with a second acid, water, a pore-enlarging agent, and an optional modified metal compound for a second treatment, filtering, drying, and obtaining the macroporous kaolinite. The modified metal compound is added in at least one step of the first treatment and the second treatment. The macroporous kaolinite can be used to prepare a cracking catalyst. The obtained catalyst has high heavy oil conversion activity, high gasoline and liquefied gas yields, low dry gas selectivity, and low coke selectivity.
[0008] CN105618107 B discloses a catalytic cracking catalyst and a preparation method thereof. The catalyst contains 10-60 wt% of titanium and / or zirconium modified Y molecular sieve, 10-60 wt% of clay and 5-50 wt% of a binder based on the total weight of the catalyst; the titanium and / or zirconium modified Y molecular sieve contains 1.0 wt%-15.0 wt% of titanium and / or zirconium metal oxide. The catalyst preparation method comprises the steps of preparing titanium and / or zirconium modified Y molecular sieve, preparing catalyst slurry and spray drying, wherein the titanium and / or zirconium modified Y molecular sieve comprises the following steps: (1) dispersing a titanium and / or zirconium-containing compound in water, and adjusting the pH value of the mixture to 3-10; (2) mixing the molecular sieve with the mixture obtained in step (1), stirring; optionally filtering and / or drying; (3) calcining at 300-700°C. The catalyst has a high heavy oil conversion capacity and gasoline yield.
[0009] In the prior art, the titanium tetrachloride-containing waste liquid generated during the preparation of polypropylene catalysts is usually separated from the titanium; the preparation process of titanium-containing kaolinite is complicated, and acid needs to be added and filtered multiple times during the preparation process; the modified ZSM-5 molecular sieve and the corresponding catalytic cracking catalyst are not used to reduce the tendency to form coke and reduce the yield of heavy oil.
[0010] Therefore, in order to solve the problem of treating a large amount of waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalysts and to solve the unfavorable factors of high heavy oil yield, high coke production and low light olefin yield during catalytic cracking, despite the recent catalyst technology, new technology for preparing catalytic cracking catalysts with simple and feasible preparation process and excellent performance is still needed. Summary of the invention
[0011] In order to solve the above problems, the purpose of the present invention is to provide a catalytic cracking catalyst and a preparation method thereof. The catalytic cracking catalyst, when used in a catalytic cracking process, can promote the conversion of heavy oil, reduce the yield of heavy oil, reduce the tendency to form coke, and at the same time have a high yield of light olefins and have excellent reaction selectivity and performance.
[0012] In order to achieve the above-mentioned object, the present invention provides a catalytic cracking catalyst, which comprises, based on 100% by weight of the catalytic cracking catalyst, 15-55% by weight of a modified ZSM-5 molecular sieve, 0-5% by weight of a high-silicon ZSM-5 molecular sieve, 0.5-10% by weight of a Y-type molecular sieve, 5-55% by weight of clay, 0-25% by weight of pseudo-boehmite, 4-70% by weight of a titanium-containing composite binder, 0-15% by weight of a binder, 0-30% by weight of an inorganic oxide carrier material, and 0-20% by weight of a Phosphorus calculated as oxide and 0-5% of modified metal compound calculated as oxide; wherein the preparation method of the titanium-containing composite binder comprises the following steps: (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the above mixture at 40-120° C. for 0.5-6h to obtain the titanium-containing composite binder; based on the dry basis of the titanium-containing composite binder as 100%, the composition of the titanium-containing composite binder comprises 7-45wt% of titanium calculated as oxide, 0.6-40wt% of aluminum calculated as oxide, and 30-92wt% of silicon calculated as oxide.
[0013] According to a specific embodiment of the present invention, preferably, the preparation method of the modified ZSM-5 molecular sieve comprises the following steps: (a) mixing a ZSM-5 molecular sieve slurry, a titanium tetrachloride solution, and one or more compounds selected from iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium, and yttrium, contacting at 4-150°C for 10 min-2 h, drying, and calcining to obtain a mixture; (b) mixing the mixture obtained in step (a) with a phosphorus-containing compound, contacting at 4-150°C for 10 min-2 h, drying, and calcining to obtain the modified ZSM-5 molecular sieve; based on the weight of the modified ZSM-5 molecular sieve being 100%, the composition of the modified ZSM-5 molecular sieve comprises 0.2-25% of titanium calculated as oxide, 0-5% of the sum of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium, and yttrium calculated as oxide, and 0.2-6% of phosphorus calculated as oxide.
[0014] According to a specific embodiment of the present invention, preferably, based on the weight of the catalytic cracking catalyst as 100%, its composition comprises: 20-50% of modified ZSM-5 molecular sieve calculated on a dry basis, 2-8% of Y-type molecular sieve calculated on a dry basis, 10-50% of clay calculated on a dry basis, 3-15% of pseudo-boehmite calculated on a dry basis, 6-40% of titanium-containing composite binder calculated on a dry basis, 0-6% of binder calculated on an oxide basis, 3-18% of phosphorus calculated on an oxide basis and 0.2-3% of modified metal compound calculated on an oxide basis.
[0015] According to a specific embodiment of the present invention, preferably, the solid content of the titanium-containing composite binder is 10-45wt%.
[0016] According to a specific embodiment of the present invention, preferably, based on the dry basis of the titanium-containing composite binder being 100%, the composition of the titanium-containing composite binder comprises 7-30wt% titanium calculated as oxide, 8-40wt% aluminum calculated as oxide, and 35-70wt% silicon calculated as oxide.
[0017] According to a specific embodiment of the present invention, preferably, in the preparation method of the titanium-containing composite binder, the mixed raw materials also include a dispersant; based on the dry basis of the titanium-containing composite binder as 100%, the content of the dispersant is less than 10%, more preferably 0.3-5%.
[0018] According to a specific embodiment of the present invention, preferably, the dispersant includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
[0019] According to a specific embodiment of the present invention, preferably, in the preparation method of the titanium-containing composite binder or the modified ZSM-5 molecular sieve, the titanium tetrachloride solution is titanium tetrachloride waste liquid; the titanium tetrachloride waste liquid is a titanium tetrachloride-containing waste liquid generated during the preparation of a polypropylene catalyst. The titanium tetrachloride solution can be pure titanium tetrachloride.
[0020] According to a specific embodiment of the present invention, preferably, in the preparation method of the titanium-containing composite binder, the clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite; more preferably, it is one or a combination of two or more of kaolin, halloysite, diatomaceous earth, halloysite and sepiolite.
[0021] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-containing composite binder, the calcination is performed at 400-900° C. for 0.5-6 h.
[0022] According to a specific embodiment of the present invention, preferably, the preparation method of the titanium-containing composite binder comprises the following steps: mixing clay calcined at 550-850°C for 1-3h, water, and waste liquid containing titanium tetrachloride to form a mixture, heating the mixture to 60-120°C and reacting for 0.5-3h to obtain the titanium-containing composite binder.
[0023] According to a specific embodiment of the present invention, preferably, in the method for preparing the titanium-containing composite binder, after the reaction in step (2) is completed, the pH value of the reaction system is 0.5-8; more preferably, an alkaline substance is used to adjust the pH value of the reaction system to 0.5-8; more preferably, the alkaline substance is selected from one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, sodium aluminate, magnesium oxide, magnesium hydroxide, magnesium carbonate, calcium oxide, calcium hydroxide, and calcium carbonate.
[0024] According to a specific embodiment of the present invention, preferably, in step (1), the clay is crushed to an average particle size D (v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.
[0025] According to a specific embodiment of the present invention, preferably, the silicon-aluminum molar ratio of the high-silicon ZSM-5 molecular sieve is greater than 200.
[0026] According to a specific embodiment of the present invention, preferably, in the preparation method of the modified ZSM-5 molecular sieve, the compound of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium is one or a combination of two or more of the oxides, chlorides, nitrates, carbonates, sulfates, oxalates and acetates of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium.
[0027] According to a specific embodiment of the present invention, preferably, in the preparation method of the modified ZSM-5 molecular sieve, the phosphorus-containing compound includes one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphoric acid, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate.
[0028] According to a specific embodiment of the present invention, preferably, in the preparation method of the modified ZSM-5 molecular sieve, the phosphorus-containing compound includes one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, magnesium phosphate, aluminum phosphate, phosphorous acid, ammonium phosphite, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.
[0029] According to a specific embodiment of the present invention, preferably, in the method for preparing the modified ZSM-5 molecular sieve, the calcination temperature in step (a) and step (b) is 450-650° C., and the calcination time is 1 h-4 h.
[0030] According to a specific embodiment of the present invention, preferably, in the preparation method of the modified ZSM-5 molecular sieve, the titanium tetrachloride solution and / or the compound selected from iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium are adjusted to pH 0.5-8 by alkaline substances and then mixed with the ZSM-5 molecular sieve slurry.
[0031] According to a specific embodiment of the present invention, preferably, in the preparation method of the modified ZSM-5 molecular sieve, the alkaline substance includes one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, magnesium oxide, magnesium hydroxide, and magnesium carbonate.
[0032] According to a specific embodiment of the present invention, preferably, based on the weight of the modified ZSM-5 molecular sieve being 100%, the composition of the modified ZSM-5 molecular sieve comprises 0.2-25% of titanium calculated as oxide, 0-5% of the sum of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium calculated as oxide, and 0.2-6% of phosphorus calculated as oxide.
[0033] According to a specific embodiment of the present invention, preferably, the modified ZSM-5 molecular sieve contains titanium and phosphorus elements, and may also contain one or more selected from the group consisting of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium elements, wherein titanium comes from the waste liquid containing titanium tetrachloride generated during the preparation of the polypropylene catalyst; and the iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium elements come from one or more of the oxides, chlorides, nitrates, carbonates, sulfates, oxalates and acetates of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium.
[0034] According to a specific embodiment of the present invention, preferably, the Y-type molecular sieve comprises HY, NH 4 Y, hydrothermal ultra-stable Y molecular sieve, silicon tetrachloride vapor phase ultra-stable Y molecular sieve, Y-type molecular sieve containing rare earth (such as yttrium), and phosphorus-modified ultra-stable Y molecular sieve, or a combination of two or more thereof; the Y-type molecular sieve containing rare earth (such as yttrium) includes an ultra-stable Y molecular sieve modified with rare earth (such as yttrium), and an ultra-stable Y molecular sieve modified with phosphorus and rare earth (such as yttrium), or a combination of two or more thereof.
[0035] According to a specific embodiment of the present invention, preferably, the clay is selected from one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite, and more preferably is one or a combination of two or more of kaolin, halloysite, diatomaceous earth, halloysite and sepiolite.
[0036] According to a specific embodiment of the present invention, preferably, the binder includes one or a combination of two or more of aluminum sol, silica sol, silica-aluminum sol, and phospho-aluminum sol.
[0037] According to a specific embodiment of the present invention, preferably, the inorganic oxide carrier material includes one or a combination of two or more of white carbon black, an alumina material containing a Br(II) acid center, and a silica-alumina material containing a Br(II) acid center; the alumina material containing a Br(II) acid center and the silica-alumina material containing a Br(II) acid center have a high pore volume, a large specific surface area, a double pore distribution, a high thermal stability and a higher acid amount, and contain a Br(II) acid center.
[0038] According to a specific embodiment of the present invention, preferably, the phosphorus comes from one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphate, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate; more preferably, the phosphorus comes from one or a combination of two or more of phosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, diammonium hydrogen phosphate, magnesium phosphate, aluminum phosphate, phosphorous acid, ammonium phosphite, sodium pyrophosphate, sodium tripolyphosphate, and sodium hexametaphosphate.
[0039] According to a specific embodiment of the present invention, preferably, the modified metal compound includes one or a combination of two or more of oxides, chlorides, nitrates, carbonates, sulfates, oxalates and acetates of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium.
[0040] According to a specific embodiment of the present invention, preferably, the composition of the catalytic cracking catalyst also includes a pore structure improver; the weight of the pore structure improver is 0.1-10% of the total weight of the catalytic cracking catalyst; more preferably 0.3-6%, further preferably 0.3-5%, to improve the pore structure, specific surface area and other properties of the catalyst.
[0041] According to a specific embodiment of the present invention, preferably, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
[0042] The catalytic cracking catalyst of the present invention can treat the waste liquid containing titanium tetrachloride generated in the process of preparing the polypropylene catalyst through the following technical scheme: (1) using the waste liquid containing titanium tetrachloride and a phosphorus compound to modify the ZSM-5 molecular sieve, thereby adjusting the acidity of the molecular sieve and improving the stability of the molecular sieve; (2) after the clay is calcined at high temperature, the crystal structure thereof changes. For example, the silicon and aluminum contained in kaolin are mainly kaolinite structures. After calcined at high temperature, the kaolinite undergoes a phase transformation to form active silicon and active aluminum. Such active silicon and active aluminum can react with acid or alkali; and titanium tetrachloride is hydrolyzed to produce titanium oxide and hydrogen chloride. The above properties of clay and titanium tetrachloride are utilized, waste liquid containing titanium tetrachloride is used to treat calcined clay, the calcined clay is mixed with water and waste liquid containing titanium tetrachloride, and hydrochloric acid produced by hydrolysis of titanium tetrachloride reacts with active aluminum in the calcined clay to prepare a composite binder containing titanium and clay; since the active aluminum in the clay reacts with the hydrochloric acid produced by hydrolysis of titanium tetrachloride, the active aluminum is separated from the clay to form medium and macropores in the clay, and at the same time, the active aluminum reacting with the hydrochloric acid and the fine titanium oxide particles produced by hydrolysis form a titanium-aluminum mixture together, and together with the above medium and macroporous clay, a composite binder containing titanium and clay is formed. This titanium-containing composite binder not only has the function of a binder, but also contains medium- and macro-pore clay components, which is beneficial to improving the pore structure of the catalyst, increasing the proportion of medium- and macro-pores in the catalyst, and improving the diffusion performance; (3) the organic matter contained in the waste liquid containing titanium tetrachloride (the waste liquid is mainly titanium tetrachloride, accounting for 80%-95% by weight, and the rest is mainly hexane, and also contains a small amount of alkoxy titanium complex (about 2-5% by weight) and a small amount of lipids) can also play the role of a template between the components of the molecular sieve or catalyst, decompose and form channels during the high-temperature treatment process of the preparation of the molecular sieve or catalyst, improve the pore structure of the molecular sieve or catalyst, and improve the diffusion performance. The utilization of the waste liquid containing titanium tetrachloride is convenient, and there is no need to separate the titanium, chlorine and organic matter in the waste liquid containing titanium tetrachloride, and does not increase equipment investment and processing costs.
[0043] The present invention also provides a method for preparing the above-mentioned catalytic cracking catalyst, which comprises the following steps: (1) mixing and slurrying the modified ZSM-5 molecular sieve, Y-type molecular sieve, clay, pseudo-boehmite, titanium-containing composite binder, binder, inorganic oxide carrier material, phosphorus compound, and modified metal compound (preferably adding a pore structure improver) to obtain a slurry; (2) spray-drying the slurry to form it, and then calcining and curing it to obtain the catalytic cracking catalyst.
[0044] According to a specific embodiment of the present invention, preferably, the modified ZSM-5 molecular sieve and Y-type molecular sieve in step (1) are sand-milled before mixing and slurrying and / or the slurry in step (2) is sand-milled before spray drying, so that the average particle size D (v, 0.5) of the modified ZSM-5 molecular sieve and Y-type molecular sieve in step (1) and / or the slurry in step (2) is less than 4 μm.
[0045] According to a specific embodiment of the present invention, preferably, the pseudo-boehmite is treated with acid and then aged at 40-90°C for 0.5-3 hours for peptization before use, or is subjected to aging treatment after mixing with other components; in the process of acid-peptization of the pseudo-boehmite, the acid is an inorganic acid, such as one or a combination of two or more of hydrochloric acid, sulfuric acid, and nitric acid.
[0046] According to a specific embodiment of the present invention, preferably, the ZSM-5 molecular sieve is a mesoporous ZSM-5 molecular sieve.
[0047] The present invention does not limit the spray drying method, and the technology known to those skilled in the art can be used, and the process conditions are, for example, the spray tower furnace temperature is controlled at 450-550° C., and the spray tail gas temperature is controlled at 200-300° C. The present invention can control the screening distribution of the spray-formed catalyst microspheres by controlling the spray forming conditions such as the spray pressure and the nozzle size.
[0048] Waste liquid containing titanium tetrachloride is generated in the process of preparing polypropylene catalyst, wherein the content of titanium tetrachloride is about 80%-95% (by weight). If it is discharged into the environment, it will inevitably cause environmental pollution and waste of resources. The catalytic cracking catalyst of the present invention has a simple and feasible preparation process, and the titanium content can be adjusted within a large range. The prepared catalytic cracking catalyst uses waste liquid containing titanium tetrachloride, which not only solves the problem of treating the waste liquid and avoids its pollution of the environment, but also reduces the high treatment cost of the waste liquid. At the same time, the performance of the titanium-containing catalytic cracking catalyst of the present invention is improved: the titanium-containing catalytic cracking catalyst prepared by the present invention is used in the catalytic cracking process, which can promote the conversion of heavy oil, reduce the yield of heavy oil, reduce the tendency of coking, and have a high yield of low-carbon olefins. DETAILED DESCRIPTION
[0049] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0050] The element contents in the following samples and catalysts were determined by X-ray fluorescence analysis. The wear index of the catalyst was analyzed by MS-C / 6 wear index analyzer produced by Shenyang Kehui Instrument Manufacturing Co., Ltd. The pore volume of the catalyst was determined by the water drop method.
[0051] The origin and specifications of the raw materials used are as follows:
[0052] (1) Waste liquid containing titanium tetrachloride (hereinafter referred to as waste liquid containing titanium tetrachloride) generated during the preparation of polypropylene catalyst: titanium content 90% (in terms of TiCl 4 ), provided by Lanzhou Chemical Research Center of PetroChina Petrochemical Research Institute; kaolin (burn-off 29wt%), halloysite (burn-off 16.6wt%), pseudo-boehmite (burn-off 36wt%), alumina sol (containing 21.6wt% alumina), silica sol (silicon oxide concentration 30wt%), ordinary ZSM-5 molecular sieve (silicon-aluminum ratio 31, mesopore volume 0.04mL / g), high-silicon ZSM-5 molecular sieve (silicon-aluminum ratio 384), GUSY-1 molecular sieve (silicon tetrachloride vapor phase ultra-stable molecular sieve, Na 2 O content 1.3wt%, RE 2 O 3 Content 2.7wt%, relative crystallinity 55%, unit cell constant Reduce by 4wt%), REHY molecular sieve (Na 2 O content 1.5wt%, RE 2 O 3 Content 8.2wt%, minus 5wt%), rare earth chloride solution (RE 2 O 3 Calculated content 289.3g / l): All are industrial products, collected from the catalyst factory of Lanzhou Petrochemical Company.
[0053] (2) Mesoporous ZSM-5 molecular sieve: Si / Al ratio 30, mesopore volume 0.29 mL / g;
[0054] (3) Diatomaceous earth (loss on ignition 2.6wt%), white carbon black: industrial products;
[0055] (4) Titanium tetrachloride, magnesium chloride, phosphoric acid (concentration 85%), diammonium hydrogen phosphate, lanthanum oxide, iron nitrate (Fe(NO 3 ) 3 9H 2 O), zirconium oxide, zirconium sulfate, polyethylene glycol, carboxymethyl cellulose: all are chemical reagents;
[0056] (5) Hydrochloric acid: concentration 36%, chemical reagent; nitric acid: concentration 65-68%, chemical reagent; ammonia water: concentration 18%, chemical reagent.
[0057] The spray drying methods of the catalytic cracking catalysts of the following Examples 1-4 and Comparative Examples 1-6 adopt the following process conditions: the furnace temperature of the spray tower is controlled at 450°C, the spray tail gas temperature is controlled at 200°C, and the particle size range of the obtained catalyst is 65-78 μm.
[0058] Example 1
[0059] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof is as follows:
[0060] 1. Preparation of modified ZSM-5 molecular sieve:
[0061] (1) 1.5 kg of mesoporous ZSM-5 molecular sieve (dry basis) was added to 3.9 L of deionized water, stirred evenly, and then 127 g of waste liquid containing titanium tetrachloride was added, the pH value was adjusted to 1.0 with ammonia water, and stirred at room temperature (25° C.) for 0.5 h to form a molecular sieve slurry, which was dried at 120° C. and calcined at 500° C. for 1 h;
[0062] (2) Mix the calcined molecular sieve of step (1) with 2.4 L of deionized water, add 73 g of phosphoric acid, stir evenly, place in an autoclave at 120° C. for 1 h, then dry at 120° C. and calcine at 500° C. for 1 h to obtain a titanium and phosphorus modified mesoporous ZSM-5 molecular sieve Z-1;
[0063] 2. Preparation of composite binder containing titanium and clay:
[0064] The kaolin was calcined at 750°C for 2 hours to obtain a calcined material, 1674 g (dry basis) of the calcined material was crushed to an average particle size D (v, 0.5) < 4 μm, 5.16 L of decationized water was added and stirred, 332 g of waste liquid containing titanium tetrachloride and 18 g of polyethylene glycol were added, the temperature was raised to 70°C, stirred for 1 hour, the pH value was 3.5, and a composite binder M-1 containing titanium and clay was obtained;
[0065] The composition of the composite binder M-1 containing titanium and clay is: 93wt% (dry basis) of kaolin roasted material, 7wt% (titanium oxide basis) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-1 containing titanium and clay is 25wt%;
[0066] 3. Preparation of catalytic cracking catalyst:
[0067] 0.66 kg of kaolin (dry basis), 1.68 kg of titanium-clay composite binder M-1, 0.24 kg of pseudo-boehmite (dry basis) and 2.9 L of deionized water were added to a pulping tank and stirred for 1 hour. Then 32 mL of hydrochloric acid was added, stirred for 0.5 hour and aged at 50°C for 2 hours. Then 1.08 kg of modified mesoporous ZSM-5 molecular sieve Z-1 (dry basis) and 120 g (dry basis) of GUSY-1 molecular sieve were added and stirred for 15 minutes. 0.223 kg of diammonium hydrogen phosphate, 0.585 kg of phosphoric acid and 30 g of carboxymethyl cellulose were added. After mixing and pulping for 1 hour, the obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm. The slurry was spray-dried and calcined at 550°C for 2 hours to obtain a catalytic cracking catalyst CAT-1.
[0068] The composition of the catalytic cracking catalyst CAT-1 is: 36 wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve Z-1, 4 wt% (dry basis) of GUSY-1 molecular sieve, 14 wt% (dry basis) of composite binder M-1 containing titanium and clay, 22 wt% (dry basis) of kaolin, 8 wt% of alumina from pseudo-boehmite, 4 wt% of phosphorus pentoxide from diammonium hydrogen phosphate, and 12 wt% of phosphorus pentoxide from phosphoric acid. The catalyst has a colloid solid content of 37%.
[0069] Example 2
[0070] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof is as follows:
[0071] 1. Preparation of modified ZSM-5 molecular sieve:
[0072] (1) 1.5 kg of mesoporous ZSM-5 molecular sieve (dry basis) was added to 3.5 L of deionized water and stirred evenly, and then 20 g of waste liquid containing titanium tetrachloride and 103 g of zirconium sulfate were added, and stirred at room temperature (25° C.) for 1.5 h to form a molecular sieve slurry, which was dried at 100° C. and calcined at 550° C. for 1.5 h;
[0073] (2) Mix the calcined molecular sieve in step (1) with 3.5 L of deionized water, add 97 g of phosphoric acid, stir evenly at room temperature (25° C.), dry at 100° C., and calcine at 550° C. for 1.5 h to obtain a titanium, zirconium, and phosphorus modified mesoporous ZSM-5 molecular sieve Z-2;
[0074] 2. Preparation of composite binder containing titanium and clay:
[0075] The halloysite was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 600° C. for 5 hours to obtain a calcined material. 1499 g (dry basis) of the calcined material was added with 7.3 L of decationized water and stirred, and 793 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 90° C., stirred for 2 hours, and the pH value was adjusted to 2.5 with ammonia water to obtain a composite binder M-2 containing titanium and clay;
[0076] The composition of the composite binder M-2 containing titanium and clay is: 83.3wt% (dry basis) of halloysite calcined material, 16.7wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-2 containing titanium and clay is 18wt%.
[0077] 3. Preparation of catalytic cracking catalyst:
[0078] 0.255 kg of kaolin (dry basis), 5 kg of composite binder M-2 containing titanium and clay, 0.18 kg of aluminum sol (alumina) and 155.5 mL of rare earth chloride solution were added to a slurrying tank and stirred for 0.5 h. Then, 1.14 kg of modified mesoporous ZSM-5 molecular sieve Z-2 (dry basis), 60 g of high-silicon ZSM-5 molecular sieve (dry basis), 0.682 kg of phosphoric acid and 15 g of polyethylene glycol were added. After mixing and slurrying for 0.5 h, the obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried and calcined at 500° C. for 1 h to obtain catalytic cracking catalyst CAT-2.
[0079] The composition of the catalytic cracking catalyst CAT-2 is: 38 wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve Z-2, 2 wt% (dry basis) of high-silicon ZSM-5 molecular sieve, 30 wt% (dry basis) of composite binder M-2 containing titanium and clay, 8.5 wt% (dry basis) of kaolin, 6 wt% of aluminum oxide from aluminum sol, 1.5 wt% of rare earth oxide from rare earth chloride solution, and 14 wt% of phosphorus pentoxide from phosphoric acid. The solid content of the catalyst gel is 32%.
[0080] Example 3
[0081] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof is as follows:
[0082] 1. Preparation of modified ZSM-5 molecular sieve:
[0083] (1) Under stirring, 792 g of waste liquid containing titanium tetrachloride and 113.6 g of ferric nitrate were added to 3.6 L of deionized water, stirred for 10 min, the pH value was adjusted to 1.5 with ammonia water, and then 1.5 kg of ordinary ZSM-5 molecular sieve (dry basis) was added, stirred at room temperature (25° C.) for 1 h to form a molecular sieve slurry, dried at 100° C., and calcined at 520° C. for 1 h;
[0084] (2) Mix the calcined molecular sieve of step (1) with 3.6 L of deionized water, add 112 g of diammonium hydrogen phosphate, stir evenly at room temperature (25° C.), dry at 100° C., and calcine at 520° C. for 1 h to obtain a titanium, iron, and phosphorus modified ZSM-5 molecular sieve Z-3;
[0085] 2. Preparation of composite binder containing titanium and clay:
[0086] The kaolin and diatomaceous earth were crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850° C. for 2.5 hours to obtain a calcined material. 900 g (dry basis) of the kaolin calcined material, 100.8 g (dry basis) of the diatomaceous earth calcined material, and 72 g of carboxymethyl cellulose were added with 2.0 L of decationized water and stirred, and 2109 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 60° C., stirred for 3 hours, and the pH value was adjusted to 3.0 with ammonia water to obtain a composite binder M-3 containing titanium and clay;
[0087] The composition of the composite binder M-3 containing titanium and clay is: 50wt% (dry basis) of kaolin calcined material, 5.6wt% (dry basis) of diatomaceous earth calcined material, 44.4wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-3 containing titanium and clay is 30wt%;
[0088] 3. Preparation of catalytic cracking catalyst:
[0089] (1) 0.75 kg of modified ZSM-5 molecular sieve Z-3 (dry basis), 0.21 kg of GUSY-1 molecular sieve (dry basis), 90 g of REHY molecular sieve (dry basis), and 45 g of zirconium oxide were added to 1.7 L of deionized water, stirred, and sand-milled to make the average particle size D (v, 0.5) of the mixed molecular sieve slurry less than 4 μm;
[0090] (2) 0.735 kg of kaolin (dry basis), 0.18 kg of diatomaceous earth (dry basis), 0.24 kg (solid content) of a composite binder M-3 containing titanium and clay, 180 g of aluminum sol (alumina), 0.54 kg of pseudo-boehmite (dry basis), 76.2 g of magnesium chloride, 15 g of lanthanum oxide and 1.6 L of deionized water were added to a pulping tank and pulped, stirred for 2 h, and then 150 g of carboxymethyl cellulose and 30 mL of nitric acid were added. After stirring for 25 min, the mixture was aged at 70° C. for 1 h and cooled to 35° C.; the mixed molecular sieve slurry having an average particle size D (v, 0.5) less than 4 μm was then added, and the pulping was continued for 0.5 h, and then the mixture was homogenized, spray dried, and calcined at 600° C. for 3 h to obtain a catalytic cracking catalyst CAT-3.
[0091] The composition of the catalytic cracking catalyst CAT-3 is: 25wt% (dry basis) of modified ZSM-5 molecular sieve Z-3, 7wt% (dry basis) of GUSY-1 molecular sieve, 3wt% (dry basis) of REHY molecular sieve, 8wt% (dry basis) of composite binder M-3 containing titanium and clay, 24.5wt% (dry basis) of kaolin, 6wt% (dry basis) of diatomite, 18wt% of aluminum oxide from pseudo-boehmite, 6wt% of aluminum oxide from aluminum sol, 0.5wt% of magnesium from magnesium chloride (calculated as magnesium oxide), 0.5wt% of lanthanum oxide, and 1.5wt% of zirconium oxide. The solid content of the catalyst is 36%.
[0092] Example 4
[0093] This embodiment provides a catalytic cracking catalyst, and the preparation method thereof is as follows:
[0094] 1. Preparation of modified ZSM-5 molecular sieve:
[0095] (1) 1.5 kg of mesoporous ZSM-5 molecular sieve (dry basis) was added to 3.9 L of deionized water, stirred evenly, and then 114 g of titanium tetrachloride was added, and the pH value was adjusted to 1.0 with ammonia water. The mixture was stirred at room temperature (25° C.) for 0.5 h to form a molecular sieve slurry, dried at 120° C., and calcined at 500° C. for 1 h;
[0096] (2) Mix the calcined molecular sieve of step (1) with 2.4 L of deionized water, add 73 g of phosphoric acid, stir evenly, place in an autoclave at 120° C. for 1 h, then dry at 120° C. and calcine at 500° C. for 1 h to obtain titanium and phosphorus modified mesoporous ZSM-5 molecular sieve Z-4;
[0097] 2. Preparation of composite binder containing titanium and clay:
[0098] The kaolin was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850°C for 2 hours to obtain a calcined material. 1674 g (dry basis) of the calcined material was added to 5.19 L of decationized water and stirred, 299 g of titanium tetrachloride and 9 g of polyethylene glycol were added, the temperature was raised to 85°C, and stirred for 4 hours. The pH value was 3.6 to obtain the titanium-clay composite binder M-4.
[0099] The composition of the composite binder M-4 containing titanium and clay is: 93wt% (dry basis) of kaolin calcined material, 7wt% (titanium oxide basis) of titanium from titanium tetrachloride, and the solid content of the composite binder M-4 is 25wt%;
[0100] 3. Preparation of catalytic cracking catalyst:
[0101] 0.345 kg of kaolin (dry basis), 4.8 kg of composite binder M-4 containing titanium and clay, 150 g of white carbon black, 0.8 kg of silica sol and 1.89 L of deionized water were added to a pulping tank and stirred for 0.5 h; then 0.9 kg of modified mesoporous ZSM-5 molecular sieve Z-4 (dry basis) and 15 g of GUSY-1 molecular sieve (dry basis) were added and stirred for 20 minutes, 0.244 kg of phosphoric acid and 15 g of carboxymethyl cellulose were added, and after mixing and pulping for 1 h, the obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried, and calcined at 800°C for 0.5 h to obtain catalytic cracking catalyst CAT-4.
[0102] The composition of the catalytic cracking catalyst CAT-4 is: 30 wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve Z-4, 0.5 wt% (dry basis) of GUSY-1 molecular sieve, 40 wt% (dry basis) of composite binder M-4 containing titanium and clay, 11.5 wt% (dry basis) of kaolin, 5 wt% of white carbon black, 8 wt% of silicon oxide from silica sol, and 5 wt% of phosphorus pentoxide from phosphoric acid. The solid content of the catalyst gel is 32%.
[0103] Comparative Example 1
[0104] This comparative example provides a catalytic cracking catalyst, and its preparation method is as follows:
[0105] 1. Preparation of modified ZSM-5 molecular sieve:
[0106] (1) 1.5 kg of mesoporous ZSM-5 molecular sieve (dry basis) was added to 3.9 L of deionized water, stirred at room temperature (25° C.) for 0.5 h to form a molecular sieve slurry, dried at 120° C., and calcined at 500° C. for 1 h;
[0107] (2) Mix the calcined molecular sieve of step (1) with 2.44 L of deionized water, add 73 g of phosphoric acid, stir evenly at room temperature (25° C.), dry at 120° C., and calcine at 500° C. for 1 h to obtain phosphorus-modified mesoporous ZSM-5 molecular sieve DZ-1;
[0108] 2. Preparation of catalytic cracking catalyst:
[0109] 1.08 kg of kaolin (dry basis), 0.24 kg of pseudo-boehmite (dry basis) and 2.3 L of deionized water were added to a pulping tank and stirred for 1 hour. Then 32 mL of hydrochloric acid was added, stirred for 0.5 hour and aged at 50°C for 2 hours. Then 1.08 kg of modified mesoporous ZSM-5 molecular sieve DZ-1 (dry basis) and 120 g of GUSY-1 molecular sieve were added and stirred for 15 minutes. 0.223 kg of diammonium hydrogen phosphate and 0.585 kg of phosphoric acid were added. After mixing and pulping for 1 hour, the mixture was homogenized, spray dried and calcined at 550°C for 2 hours to obtain a comparative catalytic cracking catalyst DCAT-1.
[0110] The composition of the catalytic cracking catalyst DCAT-1 is: 36 wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve DZ-1, 4 wt% (dry basis) of GUSY-1 molecular sieve, 36 wt% (dry basis) of kaolin, 8 wt% of alumina from pseudo-boehmite, 4 wt% of phosphorus pentoxide from diammonium hydrogen phosphate, and 12 wt% of phosphorus pentoxide from phosphoric acid. The catalyst has a gelled solid content of 37%.
[0111] Comparative Example 2
[0112] This comparative example provides a catalytic cracking catalyst, and its preparation method is as follows:
[0113] 1. A method for preparing kaolinite with a macroporous structure is as follows:
[0114] Kaolin was calcined at 750°C for 2 hours to obtain a calcined material (referred to as the first calcined material). 1680 g (dry basis, the same below) of the calcined material was added with decationized water (pH=3.1, the same below) and stirred to prepare a slurry with a solid content of 25 wt%. 5000 g of 1 mol / L hydrochloric acid and 1000 g of oxalic acid, TiCl 4 120 g of the first step product was calcined at 750°C for 2 hours to obtain a calcined material (referred to as the second calcined material). 1000 g (dry basis, the same below) of the second calcined material was added with decationized water and stirred to obtain a slurry with a solid content of 25% by weight. 2000 g of hydrochloric acid with a concentration of 1 mol / L, 500 g of oxalic acid, 500 g of polyethylene glycol, and TiCl 4 (analytical pure) 70g, heated to 70℃, stirred for 1 hour, then filtered to remove the mother liquor, the filter cake was dried to obtain macroporous kaolinite DM-1;
[0115] 2. Preparation of catalytic cracking catalyst:
[0116] 0.66 kg of kaolin (dry basis), 0.42 kg (dry basis) of macroporous kaolinite DM-1, 0.24 kg of pseudo-boehmite (dry basis) and 3.17 L of deionized water were added to a pulping tank and stirred for 1 hour. Then 32 mL of hydrochloric acid was added, stirred for 0.5 hour and aged at 50°C for 2 hours. Then 1.08 kg of modified mesoporous ZSM-5 molecular sieve DZ-1 (dry basis) and 120 g (dry basis) of GUSY-1 molecular sieve were added and stirred for 15 minutes. 0.223 kg of diammonium hydrogen phosphate and 0.585 kg of phosphoric acid were added. After mixing and pulping for 1 hour, the mixture was homogenized, spray dried and calcined at 550°C for 2 hours to obtain a comparative catalytic cracking catalyst DCAT-2.
[0117] The composition of the catalytic cracking catalyst DCAT-2 is: 36 wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve DZ-1, 4 wt% (dry basis) of GUSY-1 molecular sieve, 14 wt% (dry basis) of macroporous kaolinite DM-1, 22 wt% (dry basis) of kaolin, 8 wt% of alumina from pseudo-boehmite, 4 wt% of phosphorus pentoxide from diammonium hydrogen phosphate, and 12 wt% of phosphorus pentoxide from phosphoric acid. The catalyst has a gelled solid content of 37%.
[0118] Comparative Example 3
[0119] This comparative example provides a catalytic cracking catalyst, and its preparation method is as follows:
[0120] 1. Preparation of modified ZSM-5 molecular sieve:
[0121] (1) 1.5 kg of mesoporous ZSM-5 molecular sieve (dry basis) was added to 3.5 L of deionized water, stirred at room temperature (25° C.) for 1.5 h to form a molecular sieve slurry, dried at 100° C., and calcined at 550° C. for 1.5 h;
[0122] (2) The molecular sieve calcined in step (1) was mixed with 3.5 L of deionized water, 97 g of phosphoric acid was added, stirred evenly at room temperature (25° C.), dried at 100° C., and calcined at 550° C. for 1.5 h to obtain the phosphorus-modified mesoporous ZSM-5 molecular sieve DZ-2 of this comparative example;
[0123] 2. Preparation of modified halloysite:
[0124] The halloysite was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 600° C. for 5 hours to obtain a calcined material. 1499 g (dry basis) of the calcined material was added with 5.3 L of decationized water and stirred, and 1526 g of hydrochloric acid was added, and the temperature was raised to 90° C. and stirred for 2 hours to obtain the modified halloysite DM-2 of this comparative example. The solid content of the modified halloysite DM-2 was 18 wt%.
[0125] 3. Preparation of catalytic cracking catalyst:
[0126] 0.255 kg of kaolin (dry basis), 5 kg of modified halloysite DM-2, 0.18 kg of aluminum sol (alumina basis) and 155.5 mL of rare earth chloride solution were added into a slurrying tank and stirred for 0.5 h. Then, 1.14 kg of modified mesoporous ZSM-5 molecular sieve DZ-2 (dry basis), 60 g of high silicon ZSM-5 molecular sieve (dry basis) and 0.682 kg of phosphoric acid were added. After mixing and slurrying for 0.5 h, the mixture was homogenized, spray dried and calcined at 500 ° C for 1 h to obtain a comparative catalytic cracking catalyst DCAT-3.
[0127] The composition of the catalytic cracking catalyst DCAT-3 is: 38 wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve DZ-2, 2 wt% (dry basis) of high-silicon ZSM-5 molecular sieve, 30 wt% (dry basis) of modified halloysite DM-2, 8.5 wt% (dry basis) of kaolin, 6 wt% of alumina from aluminum sol, 1.5 wt% of rare earth oxide from rare earth chloride solution, and 14 wt% of phosphorus pentoxide from phosphoric acid. The solid content of the catalyst gel is 32%.
[0128] Comparative Example 4
[0129] This comparative example provides a catalytic cracking catalyst, and its preparation method is as follows:
[0130] 1. Preparation of modified ZSM-5 molecular sieve:
[0131] (1) Under stirring, 113.6 g of ferric nitrate was added to 4.4 L of deionized water, stirred for 10 min, and then 1.5 kg of ordinary ZSM-5 molecular sieve (dry basis) was added, stirred at room temperature (25° C.) for 1 h to form a molecular sieve slurry, dried at 100° C., and calcined at 520° C. for 1 h;
[0132] (2) The molecular sieve calcined in step (1) was mixed with 3.6 L of deionized water, 112 g of diammonium hydrogen phosphate was added, stirred evenly at room temperature (25° C.), dried at 100° C., and calcined at 520° C. for 1 h to obtain the iron-phosphorus modified ZSM-5 molecular sieve DZ-3 of this comparative example;
[0133] 2. Preparation of catalytic cracking catalyst:
[0134] (1) 0.75 kg of modified ZSM-5 molecular sieve DZ-3 (dry basis), 0.21 kg of GUSY-1 molecular sieve, and 90 g of REHY molecular sieve (dry basis) were added to 1.7 L of deionized water and stirred to form a mixed molecular sieve slurry;
[0135] (2) 1.05 kg of kaolin (dry basis), 0.18 kg of diatomaceous earth (dry basis), 180 g of aluminum sol (alumina basis), 0.54 kg of pseudo-boehmite (dry basis) and 2.2 L of deionized water were added to a slurrying tank and stirred for 2 h. Then 30 mL of nitric acid was added, stirred for 25 min, aged at 70 ° C for 1 h, and cooled to 35 ° C; then the above-mentioned mixed molecular sieve slurry was added, and the slurry was continued for 0.5 h. Then, homogenized, spray dried, and calcined at 600 ° C for 3 h to obtain a comparative catalytic cracking catalyst DCAT-4.
[0136] The composition of the catalytic cracking catalyst DCAT-4 is: 25wt% (dry basis) of modified ZSM-5 molecular sieve DZ-3, 7wt% (dry basis) of GUSY-1 molecular sieve, 3wt% (dry basis) of REHY molecular sieve, 35wt% (dry basis) of kaolin, 6wt% (dry basis) of diatomaceous earth, 18wt% of alumina from pseudo-boehmite, and 6wt% of alumina from aluminum sol. The solid content of the catalyst gel is 36%.
[0137] Comparative Example 5
[0138] This comparative example provides a catalytic cracking catalyst, and its preparation method is as follows:
[0139] 1. Preparation of modified ZSM-5 molecular sieve:
[0140] 1) 1.5 kg of mesoporous ZSM-5 molecular sieve (dry basis) was added to 3.9 L of deionized water, stirred at room temperature (25° C.) for 0.5 h to form a molecular sieve slurry, dried at 120° C., and calcined at 500° C. for 1 h;
[0141] (2) Mix the calcined molecular sieve of step (1) with 2.4 L of deionized water, add 73 g of phosphoric acid, stir evenly, place in an autoclave at 120° C. for 1 h, then dry at 120° C. and calcine at 500° C. for 1 h to obtain phosphorus-modified mesoporous ZSM-5 molecular sieve DZ-4;
[0142] 2. Preparation of catalytic cracking catalyst:
[0143] 1.545 kg of kaolin (dry basis), 150 g of white carbon black, 0.8 kg of silica sol and 5 L of deionized water were added to a pulping tank and stirred for 0.5 h; then 0.9 kg of modified mesoporous ZSM-5 molecular sieve DZ-4 (dry basis) and 15 g of GUSY-1 molecular sieve (dry basis) were added and stirred for 20 minutes, 0.244 kg of phosphoric acid and 15 g of carboxymethyl cellulose were added, and after mixing and pulping for 1 h, the resulting slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray-dried, and calcined at 800°C for 0.5 h to obtain a comparative catalytic cracking catalyst DCAT-5.
[0144] The composition of the catalytic cracking catalyst DCAT-5 is: 30wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve DZ-4, 0.5wt% (dry basis) of GUSY-1 molecular sieve, 51.5wt% (dry basis) of kaolin, 5wt% of white carbon black, 8wt% of silicon oxide from silica sol, and 5wt% of phosphorus pentoxide from phosphoric acid. The solid content of the catalyst gel is 32%.
[0145] Comparative Example 6
[0146] This comparative example provides a catalytic cracking catalyst, and its preparation method is as follows:
[0147] (1) A comparative binder containing titanium and clay without calcination, the preparation method of which is as follows:
[0148] 1674 g (dry basis) of kaolin was pulverized without calcination to an average particle size D (v, 0.5) < 4 μm, and 4.2 L of decationized water was directly added with stirring. 332 g of waste liquid containing titanium tetrachloride and 18 g of polyethylene glycol were added. The temperature was raised to 70°C and stirred for 1 hour. The pH value was adjusted to 3.5 with ammonia water to obtain a comparative binder DM-3 containing titanium and clay.
[0149] The composition of the comparative binder DM-3 containing titanium and clay is: 93wt% kaolin (on a dry basis), 7wt% titanium from a waste liquid containing titanium tetrachloride (on a titanium oxide basis), and the solid content of the comparative binder DM-3 is 25wt%.
[0150] 2. Preparation of catalytic cracking catalyst:
[0151] 0.66 kg of kaolin (dry basis), 1.68 kg of titanium-clay composite binder DM-3, 0.24 kg of pseudo-boehmite (dry basis) and 2.9 L of deionized water were added to a pulping tank and stirred for 1 hour. Then 32 mL of hydrochloric acid was added, stirred for 0.5 hour and aged at 50°C for 2 hours. Then 1.08 kg of modified mesoporous ZSM-5 molecular sieve DZ-4 (dry basis) and 120 g (dry basis) of GUSY-1 molecular sieve were added and stirred for 15 minutes. 0.223 kg of diammonium hydrogen phosphate, 0.585 kg of phosphoric acid and 30 g of carboxymethyl cellulose were added. After mixing and pulping for 1 hour, the resulting slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm. The slurry was spray-dried and calcined at 550°C for 2 hours to obtain a comparative catalytic cracking catalyst DCAT-6.
[0152] The composition of the catalytic cracking catalyst DCAT-6 is: 36 wt% (dry basis) of modified mesoporous ZSM-5 molecular sieve DZ-4, 4 wt% (dry basis) of GUSY-1 molecular sieve, 14 wt% (dry basis) of titanium-containing clay comparative binder DM-3, 22 wt% (dry basis) of kaolin, 8 wt% of alumina from pseudo-boehmite, 4 wt% of phosphorus pentoxide from diammonium hydrogen phosphate, and 12 wt% of phosphorus pentoxide from phosphoric acid. The catalyst has a gelled solid content of 37%.
[0153] Test Example 1
[0154] The catalytic cracking catalysts CAT-1, CAT-2, CAT-3, CAT-4 prepared in Examples 1, 2, 3, and 4 and the comparative catalytic cracking catalysts DCAT-1, DCAT-2, DCAT-3, DCAT-4, DCAT-5, and DCAT-6 prepared in Comparative Examples 1, 2, 3, 4, 5, and 6 were subjected to analytical tests on anti-wear performance and pore volume. The test results are shown in Table 1. Table 1 Performance test results of catalysts CAT-1, CAT-2, CAT-3, CAT-4 and catalysts DCAT-1, DCAT-2, DCAT-3, DCAT-4, DCAT-5, and DCAT-6
[0155] catalyst Wear index, m% / h Pore volume, mL / g CAT-1 0.9 0.41 CAT-2 1.2 0.42 CAT-3 1.5 0.40 CAT-4 1.1 0.43 DCAT-1 4.0 0.36 DCAT-2 3.5 0.39 DCAT-3 2.7 0.38 DCAT-4 3.0 0.37 DCAT-5 13.7 0.34 DCAT-6 3.7 0.35
[0156] The results in Table 1 show that compared with the comparative catalytic cracking catalysts DCAT-1, DCAT-2, DCAT-3, DCAT-4, and DCAT-6 prepared in Comparative Examples 1, 2, 3, 4, and 6, the catalytic cracking catalysts CAT-1, CAT-2, CAT-3, and CAT-4 prepared in Examples 1, 2, 3, and 4 of the present invention have a smaller wear index, better anti-wear performance, and a larger pore volume.
[0157] In Table 1, the wear index of DCAT-5 is too high and cannot meet the use requirements of the catalyst (generally the wear index should be lower than 3.5%). Compared with DCAT-5, the wear index of catalyst CAT-4 is low and has good anti-wear performance.
[0158] Test Example 2
[0159] This test example is used to evaluate the performance of the catalytic cracking catalysts of Examples 1-3.
[0160] The catalytic cracking catalysts CAT-1, CAT-2, CAT-3 prepared in Examples 1, 2, and 3 and the comparative catalytic cracking catalysts DCAT-1, DCAT-2, DCAT-3, DCAT-4, and DCAT-6 prepared in Comparative Examples 1, 2, 3, 4, and 6 were respectively subjected to aging treatment at 800° C. and 100% water vapor for 17 h, and then the catalytic cracking reaction performance was evaluated on a heavy oil micro-reactor evaluation device (ACE) using wax oil from Lanzhou Petrochemical Company as raw oil.
[0161] The evaluation results are shown in Table 2.
[0162] In Table 2, total liquid yield = liquefied gas yield + gasoline yield + diesel yield; coke factor = (100-conversion rate) × coke yield / conversion rate.
[0163] Table 2 Reaction selectivity evaluation results of catalytic cracking catalysts
[0164]
[0165]
[0166] In Table 2, compared with the comparative catalytic cracking catalyst DCAT-1, the reaction conversion rate of the catalyst CAT-1 prepared in Example 1 increased by 1.86 percentage points, the coke yield decreased by 0.86 percentage points, the coke factor decreased, and the yield of light olefins (ethylene + propylene + butene) increased by 4.9 percentage points, showing the characteristics of excellent heavy oil conversion, reduced coke generation and high yield of light olefins; compared with the comparative catalytic cracking catalyst DCAT-6, the catalyst CAT-1 prepared in Example 1 showed the same catalytic reaction performance characteristics; compared with the comparative catalyst DCAT-3, the reaction conversion rate of the catalytic cracking CAT-2 prepared in Example 2 increased by 1.11 percentage points, the coke yield decreased by 0.49 percentage points, the coke factor decreased, the yield of light olefins (ethylene + propylene + butene) increased by 2.2 percentage points, and the catalytic cracking reaction evaluation showed the same performance characteristics.
[0167] The results in Table 2 show that compared with the comparative catalytic cracking catalysts DCAT-1, DCAT-2, DCAT-3, DCAT-4 and DCAT-6 prepared in Comparative Examples 1, 2, 3, 4 and 6, the reaction conversion rate of the catalytic cracking catalysts CAT-1, CAT-2 and CAT-3 of the present invention is improved, the yield of heavy oil is reduced, the coke factor is reduced, and the yield of light olefins (ethylene + propylene + butene) is increased. It is explained that when the catalytic cracking catalyst provided by the present invention is used, the efficient conversion of heavy oil is promoted, the tendency to produce coke is reduced, and light olefins are produced more at the same time, and the selectivity of the catalytic cracking reaction is improved.
Claims
1. A catalytic cracking catalyst, which, based on the weight of the catalytic cracking catalyst being 100%, comprises: 15-55% of modified ZSM-5 molecular sieve calculated on a dry basis, 0.5-10% of Y-type molecular sieve calculated on a dry basis, 0-5% of high-silicon ZSM-5 molecular sieve calculated on a dry basis, 5-55% of clay calculated on a dry basis, 0-25% of pseudo-boehmite calculated on a dry basis, 4-70% of titanium-containing composite binder calculated on a dry basis, 0-15% of binder calculated on an oxide basis, 0-30% of inorganic oxide support material calculated on an oxide basis, 0-20% of phosphorus calculated on an oxide basis, and 0-5% of modified metal compound calculated on an oxide basis; in, The preparation method of the titanium-containing composite binder comprises the following steps: (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the above mixture at 40-120° C. for 0.5-6 hours to obtain the titanium-containing composite binder; Calculated on a dry basis of 100%, the titanium-containing composite binder comprises 7-45 wt % of titanium in terms of oxide, 0.6-40 wt % of aluminum in terms of oxide, and 30-92 wt % of silicon in terms of oxide; Preferably, the preparation method of the modified ZSM-5 molecular sieve comprises the following steps: (a) mixing a ZSM-5 molecular sieve slurry, a titanium tetrachloride solution, and one or more compounds selected from iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium, and yttrium, contacting at 4-150° C. for 10 min-2 h, drying, and calcining to obtain a mixture; (b) mixing the mixture obtained in step (a) with a phosphorus-containing compound, contacting at 4-150° C. for 10 min-2 h, drying and calcining to obtain the modified ZSM-5 molecular sieve; based on the weight of the modified ZSM-5 molecular sieve being 100%, the composition of the modified ZSM-5 molecular sieve comprises 0.2-25% of titanium calculated as oxide, 0-5% of the sum of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium calculated as oxide, and 0.2-6% of phosphorus calculated as oxide.
2. The catalytic cracking catalyst according to claim 1, wherein Taking the weight of the catalytic cracking catalyst as 100%, the composition thereof comprises: 20-50% of modified ZSM-5 molecular sieve calculated on a dry basis, 2-8% of Y-type molecular sieve calculated on a dry basis, 10-50% of clay calculated on a dry basis, 3-15% of pseudo-boehmite calculated on a dry basis, 6-40% of titanium-containing composite binder calculated on a dry basis, 0-6% of binder calculated on an oxide basis, 3-18% of phosphorus calculated on an oxide basis and 0.2-3% of modified metal compound calculated on an oxide basis.
3. The catalytic cracking catalyst according to claim 1 or 2, wherein: The solid content of the titanium-containing composite binder is 10-45wt%; Preferably, based on 100% dry weight of the titanium-containing composite binder, the composition of the titanium-containing composite binder comprises 7-30 wt % titanium calculated as oxide, 8-40 wt % aluminum calculated as oxide, and 35-70 wt % silicon calculated as oxide.
4. The catalytic cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, the mixed raw materials also include a dispersant; based on the dry basis of the titanium-containing composite binder being 100%, the content of the dispersant is less than 10%.
5. The catalytic cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder or the modified ZSM-5 molecular sieve, the titanium tetrachloride solution is titanium tetrachloride waste liquid; the titanium tetrachloride waste liquid is titanium tetrachloride-containing waste liquid generated during the preparation of a polypropylene catalyst.
6. The catalytic cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, the clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite.
7. The catalytic cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, the calcination is performed at 400-900° C. for 0.5-6 h; Preferably, the preparation method of the titanium-containing composite binder comprises the following steps: mixing clay calcined at 550-850°C for 1-3h, water, and waste liquid containing titanium tetrachloride to form a mixture, heating the mixture to 60-120°C and reacting for 0.5-3h to obtain the titanium-containing composite binder.
8. The catalytic cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the titanium-containing composite binder, after the reaction in step (2) is completed, the pH value of the reaction system is 0.5-8. Preferably, the pH value of the reaction system is adjusted to 0.5-8 by using an alkaline substance; Preferably, in step (1), the clay is crushed to an average particle size D(v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.
9. The catalytic cracking catalyst according to claim 1, wherein The silicon-aluminum molar ratio of the high-silicon ZSM-5 molecular sieve is greater than 200.
10. The catalytic cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the modified ZSM-5 molecular sieve, the compound of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium is one or a combination of two or more of the oxides, chlorides, nitrates, carbonates, sulfates, oxalates and acetates of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium; Preferably, in the preparation method of the modified ZSM-5 molecular sieve, the phosphorus-containing compound includes one or a combination of two or more of phosphoric acid, phosphate, phosphorous acid, phosphite, pyrophosphoric acid, pyrophosphate, polyphosphoric acid, polyphosphate, metaphosphoric acid, and metaphosphate.
11. The catalytic cracking catalyst according to claim 1 or 2, wherein: In the preparation method of the modified ZSM-5 molecular sieve, the calcination temperature in step (a) and step (b) is 450-650° C., and the calcination time is 1 h-4 h; Preferably, in the preparation method of the modified ZSM-5 molecular sieve, the titanium tetrachloride solution and / or the compound selected from iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium are adjusted to pH 0.5-8 by alkaline substances and then mixed with the ZSM-5 molecular sieve slurry.
12. The catalytic cracking catalyst according to claim 1 or 2, wherein: Taking the weight of the modified ZSM-5 molecular sieve as 100%, the composition of the modified ZSM-5 molecular sieve includes 0.2-25% titanium calculated as oxide, 0-5% the sum of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium calculated as oxide, and 0.2-6% phosphorus calculated as oxide.
13. The catalytic cracking catalyst according to claim 1 or 2, wherein: The Y-type molecular sieve includes one or a combination of two or more of HY, NH4Y, hydrothermal ultra-stable Y molecular sieve, silicon tetrachloride vapor phase ultra-stable Y molecular sieve, rare earth-containing Y-type molecular sieve, and phosphorus-modified ultra-stable Y molecular sieve; the rare earth-containing Y-type molecular sieve includes one or a combination of two of rare earth-modified ultra-stable Y molecular sieve and phosphorus- and rare earth-modified ultra-stable Y-type molecular sieve.
14. The catalytic cracking catalyst according to claim 1 or 2, wherein: The clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite.
15. The catalytic cracking catalyst according to claim 1 or 2, wherein: The inorganic oxide carrier material includes one or a combination of two or more of white carbon black, an alumina material containing a Brønsted acid center, and a silicon-aluminum material containing a Brønsted acid center.
16. The catalytic cracking catalyst according to claim 1 or 2, wherein: The modified metal compound includes one or a combination of two or more of the oxides, chlorides, nitrates, carbonates, sulfates, oxalates and acetates of iron, zinc, magnesium, calcium, zirconium, lanthanum, cerium and yttrium.
17. The catalytic cracking catalyst according to claim 1 or 2, wherein: The composition of the catalytic cracking catalyst also includes a pore structure improver; the weight of the pore structure improver is 0.1-10% of the total weight of the catalytic cracking catalyst; Preferably, the pore structure improver includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.
18. A method for preparing a catalytic cracking catalyst according to any one of claims 1 to 17, comprising the following steps: (1) mixing and slurrying the modified ZSM-5 molecular sieve, Y-type molecular sieve, clay, pseudo-boehmite, titanium-containing composite binder, binder, inorganic oxide carrier material, phosphorus compound, and modified metal compound to obtain a slurry; (2) The slurry is spray-dried to form a shape, and then calcined to solidify, thereby obtaining the catalytic cracking catalyst.
19. The preparation method according to claim 18, wherein: The average particle size D (v, 0.5) of the slurry in step (2) is less than 4 μm; Preferably, the ZSM-5 molecular sieve is a mesoporous ZSM-5 molecular sieve.
20. The preparation method according to claim 18, wherein: The pseudo-boehmite is peptized by adding acid and then aging at 40-90° C. for 0.5-3 hours before use. In the process of peptizing the pseudo-boehmite by adding acid, the acid is an inorganic acid.
Citation Information
Patent Citations
Catalytic cracking aid as well as preparation method and application thereof
CN116020548A
Method for preparing cracking assistant
CN116920932A
Cracking process
US4975180A